Yeast CA-11 fermentation in musts treated with brown and green propolis - Montijo, Nayara Abrao [UNESP]; Silva, Aline Ferreira [UNESP]; Costa, Gustavo Henrique Gravatim [UNESP]; Ferreira, Osania Emerenciano [UNESP]; Mutton, Márcia Justino Rossini [UNESP] (Academic Journals, 2014)
Worldwide laws are being created to reduce the amount of antimicrobial residues in foods and beverages. Distilled alcoholic beverages, such as cachaça should be detached, because some microorganisms infect the fermentation process and decrease the product quality, making it to require microbiological control. Thus, the objective of this research was to evaluate the green and brown propolis extract, as well as the previous physical-chemical treatment of sugarcane juice as antimicrobial agents and their effects on yeast CA-11 fermentation for cachaça production. The experiment was arranged in a completely randomized design in split splots with three replications. Main treatments constituted four antimicrobials (sodium monoensin, green propolis extract, brown propolis extract and physical-chemical treatment) and an untreated control. Secondary treatments were the five fermentation cycles. The amount of yeast cell and bud viability, yeast bud rate during the fermentation, pH, total acidity, glycerol and alcohol contents were evaluated in wines. The use of antimicrobial agents, especially the green and brown propolis extracts, improved the maintenance of the amount of live yeast cells and buds, and yeast budding rate as compared to the control treatment. Ethanol levels produced by the yeast strain ‘CA-11’ during fermentation were found to be around 6 to 7%, which are not statistically significant among the treatments. Results indicate great potential for the use of propolis as antimicrobial in fermentatiton process for production of distilled beverages, like cachaça.
Keywords: Distillate beverage; Cachaça; Antimicrobial agents; Saccharomyces cerevisiae